Recent advances in peptide-based therapeutic strategies for breast cancer treatment - Li, Ling; Duns, Gregory J.; Dessie, Wubliker; Cao, Zhenmin; Ji, Xiaoyuan; Luo, Xiaofang (Frontiers in Pharmacology, 2023)
Breast cancer is the leading cause of cancer-related fatalities in female worldwide. Effective therapies with low side effects for breast cancer treatment and prevention are, accordingly, urgently required. Targeting anticancer materials, breast cancer vaccines and anticancer drugs have been studied for many years to decrease side effects, prevent breast cancer and suppress tumors, respectively. There are abundant evidences to demonstrate that peptide-based therapeutic strategies, coupling of good safety and adaptive functionalities are promising for breast cancer therapy. In recent years, peptide-based vectors have been paid attention in targeting breast cancer due to their specific binding to corresponding receptors overexpressed in cell. To overcome the low internalization, cell penetrating peptides (CPPs) could be selected to increase the penetration due to the electrostatic and hydrophobic interactions between CPPs and cell membranes. Peptide-based vaccines are at the forefront of medical development and presently, 13 types of main peptide vaccines for breast cancer are being studied on phase III, phase II, phase I/II and phase I clinical trials. In addition, peptide-based vaccines including delivery vectors and adjuvants have been implemented. Many peptides have recently been used in clinical treatments for breast cancer. These peptides show different anticancer mechanisms and some novel peptides could reverse the resistance of breast cancer to susceptibility. In this review, we will focus on current studies of peptide-based targeting vectors, CPPs, peptide-based vaccines and anticancer peptides for breast cancer therapy and prevention.